Оптимізація техніко-економічних показників автомобільного дизеля з використанням функції бажаності Харінгтона - Клименко, Олександр Миколайович; Пильов, Володимир Олександрович; Шульга, Ігор Миколайович (НТУ "ХПІ", 2015)
Проаналізовано можливості комплексного покращення техніко-економічних показників автомобільного дизеля при використанні систем автоматичного регулювання його теплового стану. Для розв’язання компромісної задачі запропоновано використовувати узагальнену функцію бажаності Харінгтона з метою оптимізації досліджуваних показників на кожному режимі заданої моделі експлуатації. За керуючі фактори використано режимні та регулювальні параметри роботи дизеля. Оцінено ефективність різних варіантів САР.

Possibilities of complex improving of automobile diesel technical and economic parameters by use of automatic control systems of its thermal state were analyzed. The basis of this research was early obtained results of experimental investigation of diesel 4ChN12/14. Complex improvements in automobile diesel efficiency and toxicity parameters were proposed to implement by optimizing mentioned parameters for each mode of given operation model. To solve the compromise tasks proposed to use the Harrington’s desirability function. As the optimized parameters was used the specific fuel consumption, the concentration of particulate matter and nitrogen oxides in the diesel engine exhaust gas. As the controlling factors was used regime parameters (mean effective pressure, engine speed) and adjusting parameters (advance angle of fuel supply, the thermal state of the piston) of the diesel engine. The efficiency of different variants of automatic control systems was evaluated.
Optimization of automobile diesel engine techno-economic indicators with using the Harrington’s desirability function
Keywords: економічність ДВЗ; димність; тверді частки; оксиди азоту; модель експлуатації; particulate matter; nitrogen oxides; operating model